PENGARUH KONSENTRASI ARANG SEKAM PADI DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN BAWANG DAYAK (Eleutherine americanaMerr.) SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN KELAS XII SMA - Umi Salfia; Yustina Yustina; Sri Wulandari (Biogenesis, 2021)
This study aims to determine the effect of the concentration of rice husk charcoal and cow manure on the growth of Dayak onions (Eleutherine americana Merr.) And produce Student Worksheets for class XII SMA. This research was conducted in Jayapura Village, Siak Regency, in October-December 2019. This study used an experimental method with a completely randomized factorial design consisting of 2 treatments using a combination of rice husk charcoal and cow manure and each treatment was repeated as much 3 times. The parameters of this study were leaf length, number of leaves, number of tillers, leaf wet weight, and tuber wet weight. The design of LKPD development refers to the stages of the Problem Based Learning model which are simplified into the Analyze and Design stages. The results showed that the combination of rice husk charcoal and cow manure can increase the growth of Dayak onions significantly affected at a dose of 90 gr/tan (S2K2) with the best treatment on each parameter observed. The results obtained will be used as a development material for the growth and development of Class XII SMA in KD 3.1 and 4.1. The results of the design of learning tools in the form of Syllabus, RPP and LKPD.